Home training recommendations for soccer players during the COVID-19 pandemic - Azevedo, A. M.; Petiot, G. H.; Clemente, F. M.; Nakamura, F. Y.; Aquino, R. (SportRxiv, 2020)
The new coronavirus (COVID-19) is an infectious disease caused by a newly discovered virus (SARS-CoV-2). This pandemic has a major impact on people's lives, and several governments ordered extended quarantine and requested social isolation to contain the spread of COVID-19 and flatten its contagion curve. Soccer practice was also severely affected by these pandemic effects, including the postponement of several championships, which involve large audiences. This process will be also dangerous for the players in the moment of returning to matches, mainly considering the abrupt spikes in the load that may occur in a very short term (from quarantine to competitive congested fixture periods). Here, we outline the benefits of home workouts using a multidimensional approach. First, we provide practical recommendations for physical, psychological, and tactical training. Next, we propose an example of a home training program spanning one weekly microcycle for soccer players, using load control based on the rating of perceived exertion. We highlighted that is crucial to make all these exercises fun and entertaining during the self-isolation period. In addition, coaches can adopt a video meeting with the players with the purpose to maintain the relationships and clear possible doubts about the workouts. The home training recommendations discussed and proposed in this article can and should be adjusted by the coaches according to their own ideas and athletes' access to equipment (e.g., treadmills, flywheel training, virtual reality). Finally, these recommendations do not apply to athletes showing any symptoms of COVID-19; in such case, self-isolation and complete rest are mandatory.